2008
DOI: 10.1016/j.jpainsymman.2007.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and Its Risk Factors in Cancer Patients Who Seek Emergency Care

Abstract: Cancer patients visiting the emergency center (EC) are seldom assessed or treated for severe fatigue, a common symptom in sick patients due to acute medical conditions arising from cancer and cancer treatment. We provide a profile of cancer-related fatigue within the EC setting. Using a single-item screening tool derived from the Brief Fatigue Inventory, 928 patients (636 with solid tumors, 292 with hematological malignancies) triaged in the EC of a tertiary cancer center rated their fatigue at its worst in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Previous studies have shown applied to the emergency room with the most common cause of pain approximately in 34% of the patients (Swenson et al, 1995;Escalente et al, 2008;Bozdemir et al, 2009). It keeps track of nausea, vomiting and shortness of breath, respectively (Bozdemir et al, 2009;Yates and Barrett, 2010;Mayer et al, 2011;Kraft-Rovere et al, 2012;Yucel et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown applied to the emergency room with the most common cause of pain approximately in 34% of the patients (Swenson et al, 1995;Escalente et al, 2008;Bozdemir et al, 2009). It keeps track of nausea, vomiting and shortness of breath, respectively (Bozdemir et al, 2009;Yates and Barrett, 2010;Mayer et al, 2011;Kraft-Rovere et al, 2012;Yucel et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In the existing fatigue literature, from a variety of different cohorts, predictors of fatigue have included most prominently co-existing psychological symptoms and mental health factors (including the tendency toward catastrophizing) 29, 30, 3235 , co-existing pain 36, 37 , duration of cancer treatment 38 , primary disease site 39 , comorbidity 32, 4042 , and a variety of other factors. As shown in Table 2, we found that the worsening in fatigue levels varied according to baseline levels of fatigue, and our model of fatigue worsening included baseline fatigue as a significant predictor.…”
Section: Discussionmentioning
confidence: 99%
“…The 18 included studies were published between 1995 and 2011 in seven countries: USA (n09), Taiwan (n03), France (n 02), Japan (n 01), Italy (n 01), Australia (n 01), and Argentina (n01) (see Table 4) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Seventeen studies were published in English and one in French.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Although definitions were provided for 16 of the 28 Febrile neutropenia a)Fever (temp >38°C) and profound thrombocytopenia (<20×10 9 /l) [2] b)Absolute granulocyte count <500/mm 3 [5] c)Temperature >38.3°C and suspected neutropenia [12] d)Temp >38°C and absolute neutrophil count <1,000/mm 3 [14] e)Fever ≥100.4°F (in last 24 h) and ANC ≤500 cells/ml [15] f)White blood cell count <1,000/μl (or neutrophils <500/μl) with a core temperature above 38.3°C (or >38°C on 2 consecutive occasions) [16] Sepsis a) Blood: detection of microbial CO 2 by automated method of continuous blood culturing monitoring or urine: >50,000 colony-forming units of pathologic organisms/ml [15] b) Blood lactate >4 mmol/l or low BP (SBP <90 mmHg or 40 mmHg below usual) before fluid challenge or 1+ organ dysfunction (SpO 2 <95 % with fraction of inspired air O 2 >0.5, Cr >176 μmol/l or oliguria, international normalized ratio >2, Bili >78 μmol/l, Glasgow coma scale <15) [ c) Specific to abdominal pain [9] d) Generalized abdominal pain/tenderness, rebounding pain, tenderness localized in the R lower quadrant [17] e) All types of pain [7] Fatigue a) Weakness [5] b) Self-reported on 0-10 scale (severe07-10, non-severe00-6) [ [5] c) Glasgow coma scale score ≤12 [9] Dyspnea a) Shortness of breath [5,13] b) Subjective awareness of difficulty in breathing [11] Skin reactions a) All types of rash, blisters, vesicles, purpura [1] Anemia a) Hb 5.5 g/dl [2] b) Hemoglobin <8 g/dl [11] Infection a) Microbial documentation [2] b) No definition provided, but states 'confirmed' [14] Respiratory failure a) PaO 2 <60 mmHg & RR >30 breaths/min (necessitating mech. vent.)…”
Section: Type Of Symptoms and Adverse Event Definitionsmentioning
confidence: 99%
See 1 more Smart Citation